DIGITALIZATION OF THE COURT SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Pulatovich, Komolov Dilshod (PT. Antis International Publisher, 2024)
Objective: This article explores the digitalization of the judicial system in the Republic of Uzbekistan, focusing on its stages, the enhancement of judges' IT knowledge, and the integration of information technologies to improve judicial transparency and efficiency. Methods: The study employs widely accepted research methods including objectivity, historical analysis, comparative-logical analysis, and chronological sequence principles to examine the ongoing transformation. Results: The digitization process, exemplified by the